2008
DOI: 10.1177/0275074008319218
|View full text |Cite
|
Sign up to set email alerts
|

The Program Assessment Rating Tool and the Government Performance and Results Act

Abstract: This article looks at the Government Performance and Results Act (GPRA) and the Program Assessment Rating Tool (PART) and how they assess seven programs. It establishes that the PART does not adequately consider different program types and has characteristics that create a disconnection between this tool and the GPRA: It does not enter into dialogue with the GPRA regarding the choice of performance indicators; it evaluates programs through criteria that conflict with the programs' statutes or intent and penali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…Even though over time, departmental and program budget performance information has become more transparent and publicly available, how performance information is actually used and how the usage differs by agencies, program nature, and leadership structure are still a puzzle. To answer these questions, researchers often need to rely on in-depth interviews, field observations, and documentary research (Courty & Marschke, 2003;Gueorguieva et al, 2009;Ho, 2011;Kasdin, 2010;Martin & Singh, 2004). Hence, until there is a more systematic release of program performance and budget data and the process characteristics of the budgetary decision-making process, attempts to conduct any large scale quantitative analysis of performance budgeting practice and impact will remain a challenge, and the field still needs well-designed qualitative studies to provide in-depth insights on how performance information is used in the budgetary process.…”
Section: Review Of Research Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Even though over time, departmental and program budget performance information has become more transparent and publicly available, how performance information is actually used and how the usage differs by agencies, program nature, and leadership structure are still a puzzle. To answer these questions, researchers often need to rely on in-depth interviews, field observations, and documentary research (Courty & Marschke, 2003;Gueorguieva et al, 2009;Ho, 2011;Kasdin, 2010;Martin & Singh, 2004). Hence, until there is a more systematic release of program performance and budget data and the process characteristics of the budgetary decision-making process, attempts to conduct any large scale quantitative analysis of performance budgeting practice and impact will remain a challenge, and the field still needs well-designed qualitative studies to provide in-depth insights on how performance information is used in the budgetary process.…”
Section: Review Of Research Methodologymentioning
confidence: 99%
“…Some studies look at performance budgeting as a budget phenomenon and provide some theoretical discussion of the tool in the context of budget incrementalism and rationalism (Kelly & Rivenbark, 2008;Pitsvada, & LoStracco, 2002;Reddick, 2007). Others look at performance budgeting more from an organizational management perspective and examine how the structure and process, organizational nature, and managerial capacity influence the implementation and success of reforms (Gueorguieva et al, 2009;Moynihan, 2006;Sterck, 2007). There are also some who treat performance budgeting as a policy phenomenon and apply implementation theories and other policy evaluative frameworks to evaluate different performance budgeting initiatives (Greitens & Joaquin, 2010;Grizzle & Pettijohn, 2002;Long & Franklin, 2004).…”
Section: Theoretical Framework Usedmentioning
confidence: 99%
“…The evaluation was carried out by the Office of Management and Budget (OMB) by way of a structured mechanism whereby responses were converted into scores from 0 to 100. For more information, see Gilmour (2007) or Gueorguieva et al (2009). performance is more negative on agencies run by managers selected from campaign contribution or party affiliation than other politically appointed officials.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The PART, however, is not without controversy. Many have questioned the feasibility of using the PART as a "one size fits all" assessment tool for federal programs that "does not recognize congressional decisions to enact programs in different forms" (Gueorguieva et al, 2009). For example, the Center for Effective Government (2005) reported that more than 40% of all block grant programs included in the FY 2005 and FY 2006 PART reviews were scored as ineffective.…”
Section: Strengthen the Citizen Participation Requirementsmentioning
confidence: 99%